The protective effect of melatonin and amlodipine against cerebral ischemia/reperfusion-induced oxidative brain injury in rats - (:unkn) unknown (My University, 2009)
Objective: In the present study, we investigated the putative protective effect of melatonin and amlodipinc against ischemia/repcrfusion (I/R)-induced brain damage. Material and Methods: Wistar albino rats were subjected to 15 min of bilateral carotid artery occlusion followed by 24 h of reperfusion. Melatonin and amlodipinc were administered in doses of cither 10mg/kg ip or 50μg/ral icv just before reperfusion. After neurological examination the rats were decapitated. In the brain tissue samples, malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) and Na + -K+-ATPase activities, and luminol lucigenin chemilumincscence (CL) were determined. Brain edema was evaluated by the wet-dry weight method, and blood brain barrier (BBB) permeability was evaluated by the Evans Blue (EB) extravasation. Results: The neurological deficit was significantly improved in the melatonin and amlodipinc groups when compared with the vehicle-treated groups. Ischemia/repcrfusion caused a significant decrease in the brain GSH and Na + -K + -ATPase activity, which was accompanied with significant increases in the MDA level, MPO activity, and CL levels of the brain tissues. On the other hand, both melatonin and amlodipinc treatment reversed all these biochemical indices as well as brain water content alterations induced by l/R. Conclusion: These findings suggest that both melatonin and amlodipinc effectively modulate neurobehavioural and neurochemical changes in global ischemia, most probably by virtue of their antioxidant properties.
Keywords: Amlodipine; Brain; Ischemia; Lipid peroxidation; Melatonin; Reperfusion